If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = -68 + -6x Reorder the terms: 9 + 5x = -68 + -6x Solving 9 + 5x = -68 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + 5x + 6x = -68 + -6x + 6x Combine like terms: 5x + 6x = 11x 9 + 11x = -68 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 11x = -68 + 0 9 + 11x = -68 Add '-9' to each side of the equation. 9 + -9 + 11x = -68 + -9 Combine like terms: 9 + -9 = 0 0 + 11x = -68 + -9 11x = -68 + -9 Combine like terms: -68 + -9 = -77 11x = -77 Divide each side by '11'. x = -7 Simplifying x = -7
| 6x^(3/2)-30=0 | | f(x)=-x^2+4x-1 | | 5x-10=-7x-46 | | -8/7=-x-1/7x-6/7 | | h=g/2x | | 0=2x^4+x^2-36 | | 5x-10=-7x+46 | | 15x=296 | | 32/3 | | 2-5y+5=3y+10-5y | | 16-4y=-6y-4 | | 14v-171=45v-7 | | n^6-6n^4+11n^2-6=0 | | 15x^2+4b-4=0 | | X^2-1=(x+1)(x-1) | | 5(2x+3)=2(3x+8) | | 4x-3(2x-1)-4x= | | 4y=-5x-6 | | 2(4+x)-(x+4)=6 | | 3+77x=33x+9 | | 4y=5x-6 | | 4(7b-6)-4=12 | | ln(x+4)+ln(4x+1)=8 | | 7(x+1)-2x=12 | | 10x-4=8x+7 | | 24-6(x+2)=9 | | 2.5x+1.4=x+5.9 | | 5x+6=6-(3x-2) | | 7r^2s^4-63r^4s^2= | | 7x+4+2x=31 | | 4y+5x+6=0 | | 9(x-7)=10x-8 |